Potensi Penggunaan Selulosa Kelapa Sawit Sebagai Bahan Sneakers - Sherrine Olivia Tiara Wiguna; Wyna Herdiana (Fakultas Industri Kreatif Universitas Surabaya, 2023)
The solution to the problem of environmental sustainability is increasingly urgent due to the growing number of consumers which is exacerbated by the use of raw materials for the manufacture of products that are not environmentally friendly. Therefore, the demand for environmentally friendly products or bioproducts has recently become increasingly popular and has become a challenge for manufacturers to increase production and innovation, especially in the footwear sector. One of the innovations that can be used to support the bioproduct mission is the use of material fiber derived from plant waste in the form of cellulose from empty palm oil bunches which has characteristics resembling synthetic leather. The research is supported by the results of a literature study that has been carried out as well as observations in the form of experiments testing several upper materials for resistance and moisture to testing cellulose materials in the sneaker product section. The experimental results show that cellulose materials can support the application of several anatomical parts of upper sneakers with supports in the form of a combination of materials such as cowhide, synthetic materials and corduroy fabrics as supports for cellulose materials. The results of the research are expected to raise awareness among users about the use of sustainable and recyclable materials that can be applied to fashion styles that can compete with non-bioproducts.